Defining the "Community" in Community College: A National Overview and Implications for Racial Imbalance in Texas. (June 2023) - Baker, Dominique J.; Edwards, Bethany; Lambert, Spencer F. X.; Randall, Grace
At least 38 states have created service areas or "districts" for each of their community colleges. However, little is known about the geographic boundaries of community college districts and the policymaking process that defines them. We studied state policy documents nationally and the actual district boundaries of Texas community colleges to investigate the larger policymaking processes of determining boundaries. We found significant variation across the United States, including in who determines the boundaries and whether the districts have associated tuition reductions. In our case study, we also found evidence that the majority of Texas's community college districts appear to reflect their larger local environments, although a small number may exhibit evidence of racial imbalance.